(untitled) (Revista Direito em Debate, 2022)
The article was devoted to the fields of study of Law, Political Science and Economy, aiming to analyze the activity of rating agencies and its interference in national sovereignty. The hypothetical-deductive method was used. In other words, from the previous knowledge about the conceptions of sovereignty and the role of the rating agencies and beginning from the problem of the agencies’ interference in sovereignty, conjectures and hypotheses were elaborated about the intensity of this problem and the possibilities and alternatives, which were tested from a comparison with observations from Greek and Brazilian realities. These realities, in turn, were studied through the case study method, that is, from a qualitative study that included the collection and analysis of relevant data and information. From this analysis, it was concluded that although it is difficult to quantify the influence of the agencies in internal decision-making, it is clear that this interference exists and, given the impossibility of restriction or exclusion of classifications, the alternative presented is to regulate the agencies.